Video Content Marketing as a Strategy to Increase Brand Awareness of PT Trusmi Group Properties on Social Commerce TikTok - Nadya Fatia Mahendra; Rezha Dwi Lestari; Misbak; Tiara MusThiarsih (PT FORMOSA CENDEKIA GLOBAL, 2025)
In the digital era, social media marketing has become important for increasing brand awareness and expanding audience reach. TikTok has emerged as a popular platform among the people, known for its creative and interactive content. Leveraged TikTok to increase its brand awareness. The company engages in creating relevant content and exploring innovative digital marketing strategies, especially through TikTok's interactive content and promotional features, to reach a wider audience. This research aims to examine the role of TikTok in increasing brand awareness at PT Trusmi Group Housing which operates in the Property sector. By analyzing the various marketing strategies used on TikTok, and their impact on consumer perception and memory, this research is expected to provide valuable insights for companies in designing more effective digital marketing campaigns. In addition, this research will also explore the factors that influence the success of campaigns on TikTok, including content creativity, interaction with users, and the use of influencers.